Massage with methoxy method increasing breast milk production in post-cesarean section mothers - Siti Syarashinta Cahyaningsih; Krisdiana Wijayanti; Arwani Arwani (Jurnal Kesehatan Ibu dan Anak, 2021)
The mortality of infants can be affected by the nutritional status caused by infection. To avoid the risk of death and illness, breastfeeding is very important. The most important factor for breastfeeding is smooth milk production. Massage with the methoxy method can increase milk production based on baby weight indicators. The study aims to prove the effectiveness of massage using the methoxy method to increase milk production in post- cesarean section mothers. This study used a quasi-experiment with a non-randomized pretest-posttest control group design. The samples were 54 mothers with the post-cesarean section who were divided into 3 groups (the methoxy massage method, the marmet massage technique, and the control group were given breast care). The baby's weight was measured before and after intervention (day 7, day 14, and day 21). The data were analyzed using Repeated ANOVA, Friedman, Kruskal-Wallis dan Mann Whitney. The result showed that there was a difference in increasing breast milk production between the group with methoxy method massage and the marmet technique (p=0.001). The conclusion was massage with the methoxy method is more effective as its effect of 1.4 compared to the marmet technique in increasing breast milk production in post-cesarean section mothers.